Morphological analysis of legal ideology: locating interpretive divergence. Issue 1 (9th April 2018) - Lees, Emma; Shepherd, Edward
Abstract : Purpose: The purpose of this paper is to present a "manifesto" exploring a methodological approach to legal analysis, relying upon a morphological understanding of ideology. Design/methodology/approach: The authors explore ideology within law and legal culture. They examine one such ideology – rule of law – and consider how this can shape judicial decision-making. They suggest techniques by which such influences can be identified. Findings: The authors make four findings. First, following Freeden, ideology can be understood as a ubiquitous form of political thinking which seeks to fix the meanings of essentially contested concepts. Second, ideology in this sense forms an important part, but is distinguishable from the wider notion of legal culture. Considering ideology in law as a sub-system of legal culture can therefore be fruitful in providing a rich understanding of interpretive disagreements among the judiciary. Third, rule of law as an ideal is itself ideological, as it comprises contested concepts such as certainty, equality, stability and legality. It can be considered to constitute an internal ideology of law and it can be analysed how the concepts are de-contested in individual decisions. Finally, understanding this can help in the analysis of judgments in areas with high levels of administrative discretion and political contestation, such as planning and environmental law, as it helps us to understand how any particular judge sees the role of the court in its wider political context. Originality/value: The originality of the authors' approach lies in the drawing together of methodological techniques and understandings of ideology in, and in relation to, law.